2014
DOI: 10.1039/c3nr06292a
|View full text |Cite
|
Sign up to set email alerts
|

In vivo near-infrared photothermal therapy and computed tomography imaging of cancer cells using novel tungsten-based theranostic probe

Abstract: Photothermal therapy, as a physical therapeutic technique to kill cancer, has generated a great deal of interest. Photothermal agents hence play a critical role in this modern therapy. We report the use of transition metal oxides as photothermal agents based on PEGylated WO3-x nanoparticles. The well-prepared nanoparticles presented effective results during photothermal therapy both in vitro and in vivo by using near-IR laser irradiation (980 nm, 0.5 W cm(-2)). The tumor cells were effectively damaged using lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 43 publications
0
50
0
Order By: Relevance
“…Clearly, the W 18 O 49 NPs showed brighter images than that of Iodixanol, which confirmed their superior enhanced contrast ability in CT measurement. Furthermore, the contrast capability of the as-obtained W 18 O 49 NPs was also higher than that of previously reported [13,14], which might be ascribed to their ultrafine size as Sun et al reported [24]. Before translated into in vivo usage, biocompatibility of W 18 O 49 NPs was evaluated.…”
Section: Characterization Of W 18 O 49 Npsmentioning
confidence: 72%
See 1 more Smart Citation
“…Clearly, the W 18 O 49 NPs showed brighter images than that of Iodixanol, which confirmed their superior enhanced contrast ability in CT measurement. Furthermore, the contrast capability of the as-obtained W 18 O 49 NPs was also higher than that of previously reported [13,14], which might be ascribed to their ultrafine size as Sun et al reported [24]. Before translated into in vivo usage, biocompatibility of W 18 O 49 NPs was evaluated.…”
Section: Characterization Of W 18 O 49 Npsmentioning
confidence: 72%
“…Due to their strong localized surface plasmon resonance (LSPR) property and high Xray attenuating potency, TONPs integrating computed tomography (CT) contrast and photothermotherapy (PTT) capability was gained [13,14]. Unfortunately, little work has been reported concerning direct facile synthesis of water soluble TONPs within 10 nm, which merit from their significantly enhanced tumor penetration and reduced liver uptake [15].…”
Section: Introductionmentioning
confidence: 98%
“…in vivo tests confirmed that functionalized tungsten nanoparticles could label the HER‐2 metastatic lymph nodes and laser application helps to eliminate the cancer cells. Further multimodal and therapeutic effect of nanoparticles were reported by Liu, Han, et al () and Zhang et al (). Liu produce PEGylated tungsten oxide nanoparticles having photothermal therapeutic effect having good absorption rate at NIR region: in vitro studies showed nanoparticles are effective on 4T1 murine breast cancer cells; in vivo studies confirm the contrast enhancement capacity of nanoparticles.…”
Section: Nanoparticle‐based Staining Agentsmentioning
confidence: 75%
“…CT scans of C225 conjugated gold nanoparticles revealed that antibody‐conjugated nanoparticles were able to infuse in the cancer cells where PEGylated gold nanoparticles stayed in the tumor intersitium. Furthermore, lactobionic acid functionalization of gold nanoparticles for targeting hepatocellular carcinoma (Liu et al, ; Liu, Wang, et al ), cmHsp70.1 antibody‐conjugated nanoparticles for targeting Hsp70‐positive tumors (Gehrmann, Kimm, & Stangl, ), Arg‐Gly‐Asp‐D‐Phe‐Lys peptide‐modified PEGylated dendrimer‐entrapped gold nanoparticles for targeting MDA‐MB‐435 breast carcinoma cells (Li et al, ), diatrizoic acid and nucleolin‐targeted AS1411 aptamer functionalization of gold nanoparticles for CL15 tumor (Li, Kuo, Su, Lai, & Yang, ), PEGylated HER2ab functionalized gold nanoparticles for targeting KPL‐4 breast tumors (Nakagawa et al, ), γ‐polyglutamic acid nanogel loaded gold nanoparticles for targeting cancer cells (Zhu et al, ), gold nanoparticles modified with RGD peptide for targeting αvβ3 integrin‐overexpressing cancer cells (Chen et al, ) were produced. In all applications, functionalized nanoparticles were able to enhance the contrast of targeted regions.…”
Section: Nanoparticle‐based Staining Agentsmentioning
confidence: 99%
“…One recent example employs polymer-coated tungsten-oxide nanoparticles[176]. An alternative coating of poly(ethylene glycol) has been studied for both imaging and photothermal therapy[177, 178]. Sodium tungstate nanoparticles coated with D-glucuronic acid have been reported and imaged[135].…”
Section: Choice Of Elements For Spectral Ct Contrast Materialsmentioning
confidence: 99%